REASSERTING THE ROLE OF ASBAB AL-NUZUL IN CONTEXTUALIZING QURANIC TEACHINGS: A CRITICAL HERMENEUTICAL INQUIRY IN THE MODERN AGE - Fatihatun Nadliroh; Suwarno; Ahmad Yusam Thobroni (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
This article explores the epistemological significance of asbab al-nuzul (occasions of revelation) as a hermeneutical tool for contextualizing Quranic teachings in the face of contemporary interpretive challenges. While traditionally regarded as historical annotations, asbab al-nuzul provide more than background context—they serve as critical frameworks that anchor the meaning of verses to their original socio-historical settings, thus preventing misreadings in modern applications. Employing a qualitative-descriptive method within a library research framework, this study critically engages with both classical and contemporary exegetical works. The findings reveal that integrating asbab al-nuzul into modern Quranic interpretation enhances both textual fidelity and contextual relevance, especially in navigating legal, ethical, and socio-political verses. In an era marked by pluralism, shifting norms, and the reconfiguration of Islamic thought, reaffirming the role of asbab al-nuzul becomes essential for maintaining the coherence, depth, and transformative potential of the Quranic message. This study advocates for a renewed hermeneutical approach that positions asbab al-nuzul not merely as ancillary data, but as a core interpretive mechanism in contemporary Quranic studies.